2009 International Conference on Computational Science and Engineering 2009
DOI: 10.1109/cse.2009.395
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Human Computation Systems

Abstract: Abstract-Human computation is a technique that makes use of human abilities for computation to solve problems. The human computation problems are the problems those computers are not good at solving but are trivial for humans. In this paper, we give a survey of various human computation systems which are categorized into initiatory human computation, distributed human computation and social game-based human computation with volunteers, paid engineers and online players. For the existing large number of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 41 publications
0
57
0
4
Order By: Relevance
“…Several attempts have been made recently to bring order to the rapidly developing field of collaborative creation on the Internet [62,46,80]. Wikipedia showed that allowing users free reign of encyclopaedic knowledge not only empowers mass participation but also that the resulting creation is of a very high quality.…”
Section: Collaborative Creation and Collective Intelligencementioning
confidence: 99%
“…Several attempts have been made recently to bring order to the rapidly developing field of collaborative creation on the Internet [62,46,80]. Wikipedia showed that allowing users free reign of encyclopaedic knowledge not only empowers mass participation but also that the resulting creation is of a very high quality.…”
Section: Collaborative Creation and Collective Intelligencementioning
confidence: 99%
“…In the area of human computation, Yuen et al [82] identify three broad categories based on the relative maturity of the system. Initiatory systems are the earliest examples of human computation and were generally used to collect commonsense knowledge.…”
Section: Previous Frameworkmentioning
confidence: 99%
“…With the advent of online marketplaces providing an on-demand workforce for microtasks, we have seen an explosion of work utilizing human processing power to approach problems such as image labeling [21,33,73,74], digitizing text [77], annotating audio clips [44,49], and folding proteins [20]. For surveys of research in this area, please see [55,82]. While much of the work in this has shown promise in harnessing human computational power, there is a temptation to use human workers as an easy out.…”
Section: Human Computationmentioning
confidence: 99%
“…In parallel, Yuen et al (2009) also surveyed crowdsourcing applications, categorizing them into six classes: initiatory human computation, distributed human computation, social game-based human computation with volunteers, paid engineers and online players. Their survey analyzes crowdsourcing from a social gaming perspective, differentiating the classes based on game structure and mechanisms.…”
Section: Related Survey Work On Crowdsourcingmentioning
confidence: 99%